Evaluation of a biological nematicide and a root biostimulant on Meloidogyne exigua in coffee in Naranjo, Costa Rica - Quirós-Castro, Andrea (2023)
Introduction. M. exigua causes important losses in the cultivation of coffee (Coffea arabica). A common practice for its control is the use of chemical products that sometimes are not effective, are also expensive and toxic for humans and the environment. Objetive. To evaluate a biological nematicide and a radical root biostimulant as an alternative to reduce populations of M. exigua in coffee cultivation. Materials and methods. Four treatments were evaluated: a biological nematicide, a root biostimulant, a chemical control terbufos (TQ) and an absolute control (TA) in three-year-old coffee plants in which nematodes were sampled in soil and root. A randomized complete block design with four treatments and four replications was used. For the count of M. exigua before and after treatments application, the generalized linear model with negative binomial distribution of the residuals (Proc GenMod of SAS 9.2) was used. Results. No significant differences were found between treatments, that is, none of the evaluated alternatives managed to reduce the population of nematodes, on the contrary, the populations increased after three months of application. The use of the biological nematicide increased population by 88%, TQ by 30%, root bioestimulant by 137%, and finally, TA by 134%. Conclusion. One reason for the low efficacy could be related to the number of applications of the products. Therefore, it is necessary to look for new and effective alternatives to combat nematodes.  Keywords: Coffea arabica; root-knot nematode; biological nematicide.